(untitled) (International Journal of Plant Biology, 2018)
Colletotrichum gloeosporioides is proved to be a pathogenic isolate causing anthracnose disease on coffee var. Arabica in Lao PDR. Chaetomium cupreum CC3003 inhibits sporulation of C. gloeosporiodes by 42.60 % in 30 days. The tested nano CCH, nano CCE and nano CCM derived from C. cupreum CC3003 significantly inhibits C. gloeosporioides that cause coffee anthracnose at low concentrations of about 3-15 ppm. The tested nano-particles applied to inoculated coffee seedlings significantly reduce coffee anthracnose. Research and development on nano-particles extracted from fungi are necessary to discover new strategies to control plant disease.